Clinical and echocardiographic measures governing thromboembolism destination in atrial fibrillation - McBane, Robert D.; Hodge, David O.; Wysokinski, Waldemar E. (Thrombosis and Haemostasis, 2008)
Although infrequent, embolic occlusion to non-cerebral arteries may result in limb loss, organ failure, and death. The aim of this study was to define clinical and echocardiographic characteristics determining thromboembolism destination in non-valvular atrial fibrillation. An inception cohort of individuals (n=72) were identified with incident peripheral embolism in the setting of non-valvular atrial fibrillation (1995–2005). A randomly selected group of atrial fibrillation related stroke patients (n=100) were identified for comparison. Arteries of the extremities were the most common site of embolism (85%); lower extremity involvement was twice as common compared with the upper extremity. Clinical features distinguishing peripheral embolism from stroke included age > 75, heart failure and hypertension. Severe left ventricular dysfunction, spontaneous echo contrast and left atrial thrombus were 2–3 fold more common in peripheral embolism patients. Mean CHADS-2 scores were low and comparable for both groups. By multivariate analysis, age>75 years (hazard ratio [HR] 2.3, 95% confidence interval [CI] 1.3–3.9; p=0.05) was predictive of peripheral embolism. After adjustment for age > 75 years, severe left atrial enlargement (HR 1.8, 95% CI 0.99–3.1; p=0.055) and CHADS score (HR 1.2, 95% CI 0.99–1.6; p=0.06) were of borderline significance. In conclusion, several clinical and echocardiographic measures distinguish the clinical presentation of thromboembolism in non-valvular atrial fibrillation. Small emboli are destined to lodge in the cerebral circulation as a result of hydrodynamic, anatomic, and physical factors. Advanced age, atrial enlargement and other comorbidities may increase the propensity for the formation of larger thrombi which may bypass the carotid orifice merely as a function of size.
Keywords: Atrial fibrillation; peripheral embolism; stroke